The Influence of Organizational Culture and Organizational Commitment on Organizational Citizenship Behavior (OCB) of Employees of Government Sector with Work Engagement Mediation - Febrina Ramadhani; Nia Kusuma Wardhani (Dinasti Publisher, 2024)
This research examines the relationship between organizational citizenship behavior (OCB), organizational commitment (OC), and work engagement, as well as the direct and indirect effects of these factors on OCB via work engagement. This research employs a quantitative technique to examine causality. For this research, 83 participants were surveyed using SEM-PLS (Partial Least Square). Primary and secondary data were gathered via the use of questionnaires and literature reviews, respectively. Path analysis was used in the investigation. According to the findings, There is a positive and statistically significant association between organizational culture, work engagement, and OCB. Collaboration and engagement at work are positively and significantly impacted by organizational commitment. Full participation in one's work significantly improves OCB. Work engagement is a crucial mechanism via which organizational culture influences OCB for the better. Their level of involvement at work positively and significantly impacts a person's organizational commitment (OCB).